Ice Fabric Studies on a 75m-Long Core Drilled at Mizuho Camp, East Antarctica - Masayoshi NAKAWO (National Institute of Polar Research, 1974)
A 75m-long snow/ice core was drilled at Mizuho Camp, East Antarctica, by the glaciological members of the 12th Japanese Antarctic Research Expedition (1971-1972), and its density and the orientations of the c-axes of crystal grains composing it were measured immediately after recovery. It was found that the density increased with the depth, but that the average grain size was almost constant down to about 35m, at which depth it began to show a sharp increase. At depths shallower than 35 m the directions of the c-axis were almost vertical, while the fabric patterns for the samples deeper than 35 m showed a so-called girdle pattern.